2008
DOI: 10.1177/0969733008092876
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Pain and Symptoms With a Life-Shortening Intention

Abstract: This article reports the findings of a study into the role of Dutch nurses in the alleviation of pain and symptoms with a life-shortening intention, conducted as part of a study into the role of nurses in medical end-of-life decisions. A questionnaire survey was carried out using a population of 1509 nurses who were employed in hospitals, home care organizations and nursing homes. The response rate was 82.0%; 78.1% (1179) were suitable for analysis. The results show that in about half of the cases (55.8%) nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Consequently, nurses can be an important source of information for a physician who has to decide about forgoing or starting a medical treatment. Two studies performed in the Netherlands showed that nurses were involved in end-of-life decision-making by the physician in more than half of all cases [5] and [6]. The study by Van Bruchem-van de Scheur et al indicated that there were consultations between physicians and nursing staff in 56% of the decisions about intensifying drug treatment to alleviate pain or other symptoms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nurses can be an important source of information for a physician who has to decide about forgoing or starting a medical treatment. Two studies performed in the Netherlands showed that nurses were involved in end-of-life decision-making by the physician in more than half of all cases [5] and [6]. The study by Van Bruchem-van de Scheur et al indicated that there were consultations between physicians and nursing staff in 56% of the decisions about intensifying drug treatment to alleviate pain or other symptoms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, institutions are not only responsible for introducing practice guidelines in their institutions, but also for educating and stimulating their professionals to use these guidelines. It is important that not only physicians, but also nurses are involved in this, since they are often involved in medical end-of-life decisions [3][4][5][6]. Finally, practice guidelines are just a helpful tool for quality care.…”
Section: Resultsmentioning
confidence: 99%
“…However, practice guidelines for intensified alleviation of symptoms with possible life-shortening effect can be very useful in institutions, since it is a common medical end-of-life decision [15]. In this practice guideline, attention should be paid to the role of nurses, since they are often involved in this medical end-of-life decision, but their role is often unclear [4,5]. Furthermore, it should include information about the lifeshortening effects of pain medication, since there is still uncertainty about this among physicians [19].…”
Section: Existence Of Practice Guidelines On Eas and Other Medical Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with physicians, far fewer nurses are involved in the development and revision of the institutional practice guidelines on medical end-of-life decisions. However, it is also important that nurses are involved, since several research projects in The Netherlands and Belgium showed that nurses have an important role in daily end-of-life care and medical endof-life decisions [13][14][15][16].…”
Section: Development and Revision Of Institutional Practice Guidelinementioning
confidence: 99%